ICMS e os procedimentos de combate às “empresas noteiras” no Distrito Federal nos anos de 2022 e 2023 - Costa, Thiago Wagnner Freitas da (2024)
ICMS is a Brazilian state tax that is levied on the circulation of goods and services. It is a significant source of revenue for the States and the Federal District to meet the most diverse demands of society. However, to reduce the tax burden, some taxpayers use abusive tax planning, an illegal practice. It consists of using devices to reduce or avoid the payment of taxes in a way that is contrary to the law or its purpose, including the use of simulated or artificial operations, and the creation of “notary companies”. “Notary companies” are registered and formed with the purpose of carrying out fraudulent operations. They obtain a license to operate regularly, however, they do not carry out their own activities and are normally used for tax fraud. Furthermore, “notary companies” contribute to social inequality, as taxes are an important source of revenue for public works and social programs that benefit the neediest population, promoting tax justice. Tax authorities combat these companies with tax inspection procedures, seeking to ensure that taxpayers pay the taxes due and comply with due tax obligations. These activities include verifying declared information, analyzing documents and carrying out audits. During tax inspection, inspectors have the power to access taxpayers' accounting and tax information, such as records of purchases, sales, stocks, number of employees, energy bills, among others. In addition, they can carry out visits to companies to verify the compliance of operations. In this way, with the analysis of this data it is possible to combat tax evasion efficiently and effectively, identifying patterns, mining and processing data to identify “notary companies” and charging the real beneficiary of the crime against the tax order. The subject is of great relevance, as it directly impacts the increase in revenue and reduces unfair competition, promoting tax justice.